2018
DOI: 10.1038/s41598-018-34573-7
|View full text |Cite
|
Sign up to set email alerts
|

Mining latent information in PTSD psychometrics with fuzziness for effective diagnoses

Abstract: The options of traditional self-report rating-scale, like the PTSD Checklist Civilian (PCL-C) scale, have no clear boundaries which might cause considerable biases and low effectiveness. This research aimed to explore the feasibility of using fuzzy set in the data processing to promote the screening effectiveness of PCL-C in real-life practical settings. The sensitivity, specificity, Youden’s index etc., of PCL-C at different cutoff lines (38, 44 and 50 respectively) were analyzed and compared with those of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Furthermore, the economic losses reached 84.51 billion Renminbi. In addition, it placed a great psychological burden on the survivors (5). A study of 2080 Wenchuan earthquake survivors found that 40.1% of the participants suffered from post-traumatic stress disorder (PTSD) 1 year after the earthquake (6).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the economic losses reached 84.51 billion Renminbi. In addition, it placed a great psychological burden on the survivors (5). A study of 2080 Wenchuan earthquake survivors found that 40.1% of the participants suffered from post-traumatic stress disorder (PTSD) 1 year after the earthquake (6).…”
Section: Introductionmentioning
confidence: 99%